Delivering primary education in Bangladesh: enabling the field personnel - Andaleeb, Syed Saad (© 1998 Published by MCB UP Ltd., 2016)
This case study was published in the International Journal of Public Sector Management [© 1998 Published by MCB UP Ltd. ] and the definite version is available at : http://dx.doi.org/10.1108/09513559810226761 The Journal's website is at: http://www.emeraldinsight.com/doi/full/10.1108/09513559810226761